Football in the nordic countries: practices, equality and influence - Szerovay, M.; Nevala, A.; Itkonen, H. (Routledge, 2023)
This book explores football culture, organisation and development in the five Nordic countries: Denmark, Finland, Iceland, Sweden and Norway. These countries represent an important case study in sport culture, policy and management, being shaped by unique traditions in their civil society and in social welfare and public policy.